Pemberdayaan ekonomi kreatif masyarakat melalui pelatihan pembuatan dendeng udang di Desa Sungsang II, Banyuasin II - Herpandi Herpandi; Sherly Ridhowati; Rodiana Nopianti; Shanti Dwita Lestari; Indah Widiastuti (Riau Journal of Empowerment, 2021)
Sungsang II Village, Banyuasin II is an area where the livelihoods of the community are dominant as fishermen and entrepreneurs, namely trading food products. Their seafood varies, as well as their processed products. However, their well-known superior product is shrimp-based food products, especially Penaeus vannamei shrimp, abundant and non-economical. The opportunity for this service is one of the efforts to empower the community's creative economy, as hard as with the silvo-fishery programs. The method have used in this service activity, likely discourse and direct-practice, the evaluation of this achievement was using achievement measurement tools. In concluded that the achievement score was 96% based on the average test score. This training have provided to the community through community service programs could be an effort to empower the community in seeing the opportunities in existing resources for economic activities.